Princetonians, 1776-1783 : a biographical dictionary - Harrison, Richard A., 1945- (Princeton, New Jersey : Princeton University Press, 1981)
This volume, the third in a series of biographical sketches of students at the College of New Jersey (now Princeton University), is an account of the College and its alumni during the troubled years of the Revolution. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions.
Class of 1776 -- Class of 1777 -- Class of 1778 -- Class of 1779 -- Class of 1780 -- Class of 1781 -- Class of 1782 -- Class of 1783.
"Third volume in the series of biographical dictionaries of Princetonians"--Preface
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Princeton University -- Alumni and alumnae -- Biography; Princeton University; BIOGRAPHY & AUTOBIOGRAPHY -- General; Universities and colleges -- Alumni and alumnae; dictionaries; Dictionaries; Biographies; Biographies; Dictionaries; Biographies; Dictionnaires